W.G. Armstrong, The Ordinances and Charter of the City of Jeffersonville 15-17, § 3, pt. 11 (1855) - (:unkn) unknown (My University, 1855)
§ 3, Pt. 11: Prohibited discharge of any firearm, squibs, bombs, or fireworks without a license. Punished as a nuisance.
Keywords: DISCHARGE